How do you solve 26x - 9- 17x + 2= 21x - 9- 12x + 13?

1 Answer
Sep 19, 2017

See a solution process below:

Explanation:

First, group and combine like terms on each side of the equation:

26x - 17x - 9 + 2 = 21x - 12x - 9 + 13

(26 - 17)x + (-9 + 2) = (21 - 12)x + (-9 + 13)

9x + (-7) = 9x + 4

9x - 7 = 9x + 4

Now, subtract color(red)(9x) from each side of the equation:

-color(red)(9x) + 9x - 7 = -color(red)(9x) + 9x + 4

0 - 7 = 0 + 4

-7 != 4

Because these two numbers are obviously not equal there is no solution to this equation. Or, the solution is the null or empty set:

{O/}